Glucose-lowering therapies in patients with type 2 diabetes and cardiovascular diseases. (29th August 2020) - Prattichizzo, Francesco; La Sala, Lucia; Rydén, Lars; Marx, Nikolaus; Ferrini, Marc; Valensi, Paul; Ceriello, Antonio
Abstract: Type 2 diabetes mellitus is a major risk factor for developing cardiovascular disease, and many patients with diabetes have prevalent cardiovascular complications. Recent cardiovascular outcome clinical trials suggest that certain new glucose-lowering drugs are accompanied by additional cardioprotective properties. Indeed, selected glucagon-like peptide-1 receptor agonists have a proved cardiovascular benefit in terms of a reduced incidence of ischaemic events, while sodium/glucose co-transporter-2 inhibitors have also shown significant protection, with a striking effect on heart failure and renal endpoints. These findings have been integrated in recent guidelines which now recommend prescribing (when initial metformin monotherapy fails) a glucagon-like peptide-1 receptor agonist or a sodium/glucose co-transporter-2 inhibitor with clinical trial-confirmed benefit in patients with diabetes and atherosclerotic cardiovascular disease, and a sodium/glucose co-transporter-2 inhibitor in such patients with heart failure or chronic kidney disease at initial stages. Furthermore, the new 2019 European Society of Cardiology guidelines in collaboration with the European Association for the Study of Diabetes recommend a glucagon-like peptide-1 receptor agonist or a sodium/glucose co-transporter-2 inhibitor in treatment-naive patients with type 2 diabetes mellitus with pre-existing cardiovascular disease or at high cardiovascular risk. Future research will disentangle the mechanisms underpinning these beneficial effects and will also establish to what extent these results are generalisable to the whole diabetes population. In the meantime, available evidence should prompt a wide diffusion of these two classes of drugs among patients with diabetes and cardiovascular disease. Here, we briefly summarise recent findings emerging from cardiovascular outcome clinical trials, discuss their impact on treatment algorithms and propose new possible approaches to improve our knowledge further regarding the cardiovascular effect of glucose-lowering medications.